Wideband Planar Monopole Antennas for Gps/Wlan and X-Band Applications - Bozdağ, Göksenin; Kuştepeli, Alp; Kuştepeli, Alp (John Wiley and Sons Inc., 2016)
In this article, two printed planar monopole antennas (PPMA) are presented. In the design of the first PPMA, the structure is divided into sections and they are optimized in the sense of bottom to up strategy. Tapered transitions and inset feed are employed to increase the bandwidth. The antenna operates between 2.37 GHz and 12 GHz with VSWR<2 and an average peak realized gain of 4.95 dB. Therefore, it is suitable for WLAN, WiMAX, UWB, and X-Band applications. The second PPMA is designed by implementing slots on the previous one to include GPS. The resulting antenna operates in the 1.38-1.60 GHz and 2.33-13.74 GHz bands with VSWR<2. As a result, it also includes GPS in addition to the previous bands. The peak realized gain in GPS is 0.47 dB at 1.575 GHz and the average peak realized gain is 4.41 dB for the 2.33-13.74 GHz band. The group delay performances of the proposed PPMAs are also examined and the maximum group delay deviations of the first and the second PPMAs are observed as 1 ns and 1.33 ns, respectively.
Keywords: Microwave antennas; Wideband antennas; Planar monopole antenna; Slotted antennas